Sign Language Mathematics Lecture Video as Assistive Technology for Inclusive Class in Higher Education - Sugiman, Sugiman; Suyitno, Amin; Pujiastuti, Emi; Sugiharti, Endang; Wusqo, Indah Urwatin (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
This research was motivated by the acceptance of one deaf student in the Department of Computer Science UNNES in the 2020/2021 academic year. Therefore, this research aims to provide the study with efforts to increase the absorption of deaf students in the inclusive class through the discovery of Assistive Technology. The method used in this research is Mixed Method with a qualitative and Research Development (RD) approach. Data collection includes class observations, interviews, triangulation of results, and stages of RD. Research activities include: (1) lecturer of mathematical courses made PPt files, filled in Lecturer's Voice, and filled in Sign Language. (2) Video tested in inclusive class. (3) Finalization of Assistive Technology Videos and the results were noted. Research Results: (1) multi-function video prototypes were obtained for deaf students in inclusive classes in mathematical courses. (2) There was an increase in the activity and absorption of students in the inclusive class. In conclusion, it is necessary to make assistive technology in the form of learning videos that contain sign language to increase the absorption of deaf students in the inclusive class in mathematical courses.Penelitian ini dilatarbelakangi telah diterimanya satu mahasiswa Tunarungu pada Jurusan Ilmu Komputer UNNES pada tahun ajaran 2020/2021. Oleh karena itu tujuan penelitian ini adalah memberikan kajian upaya meningkatkan daya serap mahasiswa Tunarungu di kelas Insklusif melalui penemuan Teknologi Asistif. Metode dalam penelitian ini menggunakan metode mixed method dengan pendekatan kualitatif dan Research Development (RD). Pengumpulan data meliputi; observasi kelas, wawancara, triangulasi hasil, dan tahapan RD. Kegiatan penelitian meliputi: (1) dosen pengampu mata kuliah matematis membuat file PPt, diisi suara dosen, dan diisi Bahasa Isyaratnya. (2) Video diujicobakan di kelas Inklusif. (3) Finalisasi video Teknologi Asistif dan dicatat hasilnya. Hasil penelitian: (1) Diperoleh Prototip video Multi-Fungsi untuk mahasiswa Tunarungu di kelas Inklusif pada mata kuliah matematis. (2) Ada peningkatan aktivitas dan Daya Serap mahasiswa di kelas Inklusif. Kesimpulannya: Untuk meningkatkan daya serap mahasiswa Tunarungu di kelas Insklusif pada mata kuliah matematis, perlu dibuat Teknologi Asistif berupa video pembelajaran yang berisi Bahasa Isyarat.